2023
DOI: 10.1021/acs.langmuir.2c03085
|View full text |Cite
|
Sign up to set email alerts
|

On Nanobubble Dynamics under an Oscillating Pressure Field during Salting-out Effects and Its DLVO Potential

Abstract: We have investigated the origin, stability, and nanobubble dynamics under an oscillating pressure field followed by the salting-out effects. The higher solubility ratio (salting-out parameter) of the dissolved gases and pure solvent nucleates nanobubbles during the salting-out effect, and the oscillating pressure field enhances the nanobubble density further as solubility varies linearly with gas pressure by Henry’s law. A novel method for refractive index estimation is developed to differentiate nanobubbles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…However, in our previous study, we proposed a single nanobubble stability model in which stability was shown for nanobubbles in pure water and in salt (mono, di, and trivalent salts) solutions. 36 Here, we considered the force balance around a single nanobubble to predict the equilibrium size of a nanobubble in pure alcohols. The force balance model around a single nanobubble may be helpful in predicting the stability of a swarm of nanobubbles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in our previous study, we proposed a single nanobubble stability model in which stability was shown for nanobubbles in pure water and in salt (mono, di, and trivalent salts) solutions. 36 Here, we considered the force balance around a single nanobubble to predict the equilibrium size of a nanobubble in pure alcohols. The force balance model around a single nanobubble may be helpful in predicting the stability of a swarm of nanobubbles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It can also be speculated that a single nanobubble may not exist, but a swarm of nanobubbles exists due to the mutual repulsion from the surrounding negatively charged nanobubbles. However, in our previous study, we proposed a single nanobubble stability model in which stability was shown for nanobubbles in pure water and in salt (mono, di, and trivalent salts) solutions . Here, we considered the force balance around a single nanobubble to predict the equilibrium size of a nanobubble in pure alcohols.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations